Enzastaurin before and concomitant with radiation therapy, followed by enzastaurin maintenance therapy, in patients with newly diagnosed glioblastoma without MGMT promoter hypermethylation - Wick, Wolfgang; Steinbach, Joachim P.; Platten, Michael; Hartmann, Christian; Wenz, Frederik; Von Deimling, Andreas; Shei, Peipei; Moreau-Donnet, Valerie; Stoffregen, Clemens; Combs, Stephanie E. (Neuro-Oncology, 2013)
BackgroundThis study's primary objective was evaluation of the progression-free survival rate at 6 months (PFS-6) in patients with newly diagnosed glioblastoma without O6-methylguanine-DNA-methyltransferase (MGMT) promoter hypermethylation postsurgically treated with enzastaurin before and concomitantly with radiation therapy, followed by enzastaurin maintenance therapy. PFS-6 of at least 55% was set to be relevant compared with the data of the EORTC 26981/22981 NCIC CE.3 trial.MethodsAdult patients with a life expectancy of at least 12 weeks who were newly diagnosed with a histologically proven supratentorial glioblastoma without MGMT promoter hypermethylation were eligible. Patients were treated with enzastaurin prior to, concomitantly with, and after standard partial brain radiotherapy. Here we report on a multicenter, open-label, uncontrolled phase II study of patients with newly diagnosed glioblastoma without MGMT promoter hypermethylation treated with enzastaurin and radiation therapy within 4 study periods.ResultsPFS-6 was 53.6% (95% confidence interval [CI]: 39.8-65.6). The median overall survival was 15.0 months (95% CI: 11.9-17.9) for all patients, 3.9 months (95% CI: 0.8-9.0) for patients with biopsy, 15.4 months (95% CI: 10.1-17.9) for patients with partial resection, and 18.9 months (95% CI: 13.9-28.5) for patients with complete resection. The safety profile in this study was as expected from previous trials, and the therapy was well tolerated.ConclusionsPFS-6 missed the primary planned outcome of 55%. The secondary exploratory analysis according to resection status of the different subgroups of patients with biopsies, partial resection, and complete resection demonstrates the strong prognostic influence of resection on overall survival. © 2013 © The Author(s) 2013. Published by Oxford University Press on behalf of the Society for Neuro-Oncology. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.
CRIS-Team Scopus Importer:2023-03-08
Keywords: brain tumors; enzastaurin; glioblastoma; MGMT; radiotherapy